Agronomic Evaluation of Potato (Solanum tuberosum L.) Genotypes for Tuber Yield and Yield Attributing Traits - Tsagaye, Dasta; Fikre, Demis; Fufa, Nimona; Gebretensay, Fekadu; Ali, Awoke; Wegayehu, Gizaw (International Journal of Bio-resource and Stress Management, 2023)
The experiment was carried out under rain fed conditions for three consecutive years (2017–2019) from mid-June to mid-October at Bekoji and Kofele sub sites of Kulumsa Agricultural Research Center, Ethiopia by using improved varieties to identify superior genotypes. The experiment was laid out in a randomized complete block design with three replications. The results of analysis of variance (ANOVA) showed that the presence of significant (p<0.05) differences among genotypes for all traits studied. Analysis of variance revealed that location by year effect had highly significant difference at (p<0.01) for all traits except specific gravity which showed significant difference at (p<0.05). Treatment by location showed significant difference except stem number plant-1, total yield, and specific gravity. Treatment by year showed significant differences except for days to flowering. The highest marketable tuber yield was obtained from genotype CIP 395037.107 followed by variety Belete and CIP 395015.6 genotype. Simple correlation analysis revealed that total tuber yield showed strongly and positively significant correlation with average stem number plant-1, stem height and marketable yield. Thus, it could be concluded that genotypes, year and location variations as well as their interaction had considerable influence on tuber yield and the potato’s attributes. The significant interaction effects of genotypes, location, year and positive and strong association between total yield and other traits indicates the need to test potato genotypes over season and location in order to select stable and high yielder genotypes.